Interoperable Privacy-Aware E-Participation within Smart Cities. - Patsakis, Constantinos; Laird, Paul; Clear, Michael; Bouroche, Melanie; Solanas, Agusti (Computer (00189162), 2015)
Sharing data via information and communications technology is a fundamental goal of e-government, but data fusion and data mining could reveal sensitive personal information. A proposed cryptographic protocol guarantees citizens' privacy through data aggregation and fosters e-participation in a scalable and interoperable way. The Web extra at http://youtu.be/xTcHNhC3cHw is an audio recording of Computer magazine Editor in Chief Sumi Helal interviewing Constantinos Patsakis about a cryptographic protocol that guarantees citizens privacy through data aggregation and fosters e-participation in a scalable and interoperable way.